2015
DOI: 10.1371/journal.pone.0140195
|View full text |Cite
|
Sign up to set email alerts
|

Hemodialysis versus Peritoneal Dialysis: A Comparison of Survival Outcomes in South-East Asian Patients with End-Stage Renal Disease

Abstract: BackgroundStudies comparing patient survival of hemodialysis (HD) and peritoneal dialysis (PD) have yielded conflicting results and no such study was from South-East Asia. This study aimed to compare the survival outcomes of patients with end-stage renal disease (ESRD) who started dialysis with HD and PD in Singapore.MethodsSurvival data for a maximum of 5 years from a single-center cohort of 871 ESRD patients starting dialysis with HD (n = 641) or PD (n = 230) from 2005–2010 was analyzed using the flexible Ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 29 publications
3
32
0
6
Order By: Relevance
“…The mortality rates of dialysis patients were obtained from a study investigating survival outcomes of 871 incident ESRD patients in Singapore . Due to the lack of survival data for CAPD and APD patients, we assumed that the mortality rates were the same for both PD modalities.…”
Section: Methodsmentioning
confidence: 99%
“…The mortality rates of dialysis patients were obtained from a study investigating survival outcomes of 871 incident ESRD patients in Singapore . Due to the lack of survival data for CAPD and APD patients, we assumed that the mortality rates were the same for both PD modalities.…”
Section: Methodsmentioning
confidence: 99%
“…Reports indicating that they have similar effects on survival were also available. 13 In our study, We aimed to evaluate cytokines, adipocytokines and inflammatory markers in patients with CRF undergoing CAPD and HD.…”
Section: Introductionmentioning
confidence: 99%
“…From 3 years and more, HD reported a survival advantage over PD [44, 45, 47, 48]. In our SR, we included studies with a follow-up time up to 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…The patients in the included studies in our SR did not differ significantly in comorbidity, including diabetes, and were similar in age, at baseline. It has been shown that for patients above 65 with diabetes or cardiovascular disease, there may be a survival advantage in the HD group [47]. However, an SR from 2014 [49] showed that there is inconsistent evidence to which modality is the best initial treatment for diabetics patients with ESRD.…”
Section: Discussionmentioning
confidence: 99%